Student Worksheet Development to Practice Critical Thinking Skill Using Blended Learning on Reaction Rate - Intan Novitasari; Bertha Yonata (Universitas Islam Indonesia, 2021)
ABSTRACT: This research aims to determine the feasibility of student worksheets to practice critical thinking skills using blended learning on reaction rate matter. This research is using Research & Development (R&D) design with the subjects are 2nd-grade students. The instrument used which as the student worksheet, pretest-posttest sheet, student activity observation, and student responses questionnaire. The validity of the student worksheets on the concentration factor, surface area, temperature, and catalyst obtained the percentage respectively 89.37%, 87.55%, 87.67%, and 87.53%. Student activities, obtaining a percentage of 90% and observation of student responses by 91%. The effectiveness of the students' worksheets in terms of the N-gain score of the pretest and posttest with an average of 0.65 in the medium category is very effective to practice critical thinking skill. So the student worksheet using guided inquiry learning model and blended learning strategy in reaction rate matter to practice critical thinking skill is feasible to use in High School.Keywords: student worksheet, critical thinking skill, blended learning, the reaction rate